A new analysis framework for agility in the fashion industry. (1st January 2012) - Lemieux, Andrée-Anne; Pellerin, Robert; Lamouri, Samir; Carbone, Valentina
Fashion consumers are constantly demanding more variety of designs, better quality and service, including both reliability and faster delivery. The achievement of these objectives implies new relations, innovative processes and new modes of evaluation between supply chain stakeholders. These pressures have prompted academics and industrial leaders to investigate new methods in order to achieve effectiveness across the fashion supply chain. As such, the concepts of agile supply chain, flexible systems, and quick response have emerged and have been adopted in several ways in the industry. Despite their recognition, these concepts are often confused in the literature. To avoid those issues, this paper aims at proposing a formal analysis framework, called ASO, for conducting a literature review of the agility initiatives and models developed for the fashion industry. The proposed framework identifies key dimensions in terms of action levers related to supply chain agility, scope of improvement initiatives, and targeted objectives.